Croatian-Serbian disputes concerning the language and alphabet in the Triune Kingdom, 1848–1861 - Sotirović, Vladislav B. (Slavistica Vilnensis, 2004)
The goal of this study is to explore the role of language and alphabet in constructing the national identities and ideologies of the Croats and Serbs from the territory of the Triune Kingdom of Dalmatia, Croatia and Slavonia, from the beginning of the Revolution of 1848/1849 to the first session of the Croatian-Slavonian Parliament (Sabor) in Zagreb in 1861, during the period of the Austrian chancellor Alexander Bach, who attempted to centralize the multiethnic and multilinguistic Habsburg Empire administratively. The study reaches the following conclusions: 1) The South Slavs within the Habsburg Monarchy had been deeply imbued with linguistic nationalism after the Revolution of 1848/1849 as a reaction against the intolerant minority policy by the leaders of the Hungarian uprising and revolution against the Habsburgs. What the Hungarian liberals required from the Habsburgs as national rights in the Habsburg Monarchy they did not wish to be granted to non-Hungarians within the greater Hungarian Kingdom, which included Croats and Serbs in the Triune Kingdom. The Hungarian liberals intended for only ethnolinguistic Hungarians to enjoy the rights of a “political nation”, and thus, in their view, the Hungarian language had to be the only official/public medium of communication in a greater historical Hungary. 2) There are two basic reasons for the expression of linguistic nationalism by Croats and Serbs in the Triune Kingdom after 1849: a) a deep conviction by both that language and script (in addition to confession) were the crucial cornerstones of national identity; and b) a reaction to the decisions by the Hungarian Parliament (Dieta) in 1839–1840 and 1843–1844 to introduce Hungarian as the official language in all provinces of the Hungarian Kingdom. 3) Serbian linguistic nationalism was basically aimed against the Croatian attempt to impose Croatian as the sole official language within Dalmatia, Croatia and Slavonia (in 1847 and later) and to proclaim only ethnic Croats as holders of full-scale political rightse. In other words, Serbian linguistic nationalism was a protest against the Croatian policy of ethnolinguistic assimilation of the Serbs in the Triune Kingdom. 4) Both the Croats and Serbs understood the Hungarian requirement of the Hungarian (Magyar) language as the sole official language in a greater historical Hungary as an attempt both to Magyarize all non-Hungarians and to homogenize the multiethnolinguistic Hungarian Kingdom. 5) Proof that the Central European Romanticist idea of language as a pivotal national determinator was sincerely accepted by the South Slavs within the Habsburg Monarchy is the fact that the Croatian and Serbian national intelligentia neglected the use of the Landsprache, but fought for the using a language or languages named after their own ethnic group(s) (Croatian and Serbian) in public affairs. 6) The Serbs in the Triune Kingdom politically struggled for inclusion of the Serbian ethnic name into the compound name for the official language in public use in Dalmatia, Croatia and Slavonia (i.e., the Croato-Serbian language) in order to preserve their national identity within these provinces and to fight against Croatization of their ethnolinguistic identity.